Aziridines and aziridinium intermediates in the asymmetric synthesis of beta-substituted-alpha-amino acids and 1,2,3,4-tetrahydroisoquinolines - Frost, A (2015)
This thesis is concerned with the development of methodology for the regioselective ring-opening of aziridines and aziridinium intermediates and its subsequent application to the asymmetric synthesis of β-substituted-α-amino acids and 1,2,3,4-tetrahydroisoquinolines. Chapter 1 introduces methods for the formation of aziridines and aziridinium ions and focusses on their utility as intermediates in synthesis. Chapter 2 describes studies into the synthesis of aziridines from enantiopure α-hydroxy-β-amino esters and their subsequent conversion to the corresponding β-hydroxy-α-amino acids via either a regioselective ring-opening with Cl3CCO2H, or a rearrangement promoted by Cl3CCO2H. Application of this procedure to both syn- and anti-configured substrates enabled the syntheses of (S,S)-allo-threonine, (2R,3S)-threonine, (R,R)-3-hydroxyphenylalanine and (2S,3R)-3-hydroxyphenylalanine. Chapter 3 details attempts to truncate the synthesis described in Chapter 2 by investigating the synthesis of enantiopure anti-β-hydroxy-α-amino acids via the intermediacy of aziridinium ions. These studies culminated in the development of a regioselective and stereospecific one-pot aziridinium formation and ring-opening protocol, leading to the synthesis of a range of C(3)-aryl and C(3)-alkyl substituted anti-β-hydroxy-α-amino acids. Chapter 4 discusses the conversion of enantiopure anti-α-hydroxy-β-amino esters to anti-β-fluoro-α-amino esters via the regioselective and stereospecific ring-opening of an aziridinium intermediates in situ. The subsequent development of a one-pot deprotection strategy leads to a concise and expedient synthesis of anti-β-fluorophenylalanines. The extension of this methodology to access a representative anti-α,β-diamino acid is also demonstrated. Chapter 5 describes the development of a one-pot diastereoselective rearrangement of enantiopure α-hydroxy-β-amino esters to 1,2,3,4-tetrahydroisoquinolines. The substrate scope of this reaction manifold is examined and application to the asymmetric synthesis of enantiopure 1,2,3,4-tetrahydroisoquinolines also discussed. Chapter 6 contains full experimental procedures and characterisation data for all compounds synthesised in Chapters 2, 3, 4 and 5.